PERTUMBUHAN INDUSTRI ASURANSI JIWA DI INDONESIA: SUATU KAJIAN DARI SISI PENAWARAN - Djaelani, Firdaus (Sekolah Pascasarjana UGM, 2011)
Life insurance has become the need in today modern communityâs life. In Indonesia, the demand on life insurancegrew continuously in line with the increase of peopleâs income and awareness on the importance of risk anticipation.To fulfill this demand, the number of life insurance companies always increased as well as various products suppliedin the market. However, the contribution of insurance industry, especially life insurance, on Indonesiaâs economywas relatively low. This research is aimed to analyze factors affecting the life insurance industry growth fromsupply side. The secondary data was collected from 15 biggest life insurance companies in Indonesia. Meanwhile,the main tools of analysis used were including descriptive statistic and dynamic panel regression. The analysisresult shows that the product variety has no impact on the gross premium of life insurance growth, number ofpolicies, and insurance funds. On the reverse, supporting infrastructures and government policy have significantand positive impacts.